Empowerment of Poor Communities Through Information Technology Based Entrepreneurship Training in Padang Sarai Village, Koto Tangah District, Padang City - Klub harahap, Mhd Tanwir; Setiawati, Setiawati (Universitas Negeri Padang, 2023)
This research was motivated by the many government assistance programs carried out to improve the welfare of poor people in the youth center of Padang Sarai sub-district, Koto Tangah sub-district, Padang city. Among the programs is the empowerment of poor communities through education and entrepreneurship training consisting of workshops, skills training and the formation of information technology-based business groups. This type of research uses qualitative research, using descriptive methods. The descriptive method aims to describe, summarize various conditions, various situations, or various phenomena of social reality that exist in society which is the object of research and attempts to draw that reality to the surface as a description of certain conditions, situations or phenomena. The results of this research are 1) there is an increase in the participants' ability to understand the concepts in the program, as seen from the participants' ability to utilize the program, 2) there is an increase in the participants' ability to use the program, as seen from the participants' ability to create interesting works around the material. given, 3) changes in the participants' thinking paradigm to become more logical and analytical, which can be seen from the increased enthusiasm for entrepreneurship (independence), 4) Increased knowledge of the workforce with life skills in the form of skills training in order to provide opportunities to get work.